Milk allergy most burdensome in multi‐food allergic children. Issue 7 (17th June 2020) - Abrams, Elissa Michele; Kim, Harold; Gerdts, Jennifer; Protudjer, Jennifer Lisa Penner
Abstract: Background: Food allergy is a substantial health burden, which disproportionately affects children. Among children with food allergy, as many as 70% have multiple food allergies. Whereas the overall burden of food allergy on quality of life has been described, little is known about the burden of individual allergens. We aimed to examine the perception of burden among families with multiple food‐allergic children. Methods: Parents of children with 1 + children with multiple food allergies including milk responded to online questions, including both open‐ended and closed‐ended questions on food allergy–related burdens of time, financial costs, social restrictions, and emotional demands. Results: Overall, 64 children (69.8% boys) of whom (73.0%) most were aged 10 and younger were included. Most had been diagnosed with food allergy in infancy and by a (pediatric) allergist. Other common allergies included peanut (65.6%), tree nuts (57.8%), egg (76.6%), and sesame (31.3%). Quantitatively, milk allergy was reported as carrying the most burden, including most socially limiting (81.5%), requiring the most planning (75.9%), causing the most anxiety (68.5%), most challenging to find "safe" or allergy‐friendly foods (72.2%), and costly (81.5%). Qualitatively, we identified five themes that captured burdens associated with costs, marketing of milk products to children, risk of cross‐contamination, ubiquity of milk/dairy and public confusion with lactose intolerance, and an unwillingness of others to accommodate the allergy. Conclusion: Parents whose children have multiple food allergies, including milk, report milk as the allergy associated with the greatest time, financial, social, and emotional burdens.